The Effects of Planning and Coordination towards Work Effectiveness at Faculty of Business and Management in Widyatama University, Bandung - Budiawan, Andi; Haizam Mohd Saudi, Mohd; Sutisna, Deden (International Journal of Engineering and Technology, 2018)
This research was conducted to find out how big the influence of planning and coordination partially or simultaneously towards the effectiveness of the work of permanent lecturer of Faculty of Business and Management at Widyatama University of Bandung. Research period is from June to November 2017. The population is 58 lecturers. Technique of multiple linear regression data analysis has been used using SPSS version 18 software. Regression Analysis result there is significant influence by planning variables and coordination either partially or simultaneously. Corresponding analysis based on Pearson correlation coefficient (R) obtained results of 0.831 means the relationship between planning and coordination with the effectiveness of employees is very strong. Through the value of R Square (R2) of 0.894, it can be said that the amount of coefficient of determination (KD) of 86.70% means that the effectiveness of employees 86.70% influenced by the variables of planning and coordination and the remaining 10.60% influenced by other factors not examined.Â